The Role of Work Motivation in Mediateing the Influence of Leadership and Organizational Culture on Employee Performance at Regional Personnel Agency, Raja Ampat District - Abdul Faris Umlati; Ida Bagus Udayana Putra; I Made Suniastha Amerta (Universitas Warmadewa, 2025)
The research aims to analyze the role of work motivation in mediating the influence of leadership and organizational culture on the performance of employees of the Regional Civil Service Agency of Raja Ampat Regency. The samples used in this research was 30 employees with a sampling technique using census techniques. The data analysis is using SEM-PLS inferential analysis. The results of this research indicate that leadership has a positive and insignificant effect on employee performance. Leadership has a positive and significant effect on employee work motivation. Organizational culture has a negative and insignificant effect on employee performance. Organizational culture has a positive and significant effect on work motivation. Work motivation has a positive and significant effect on employee performance. Work motivation mediates fully (full mediation) between the influence of leadership on employee performance. Work motivation mediates fully (full mediation) between the influence of organizational culture.